Історичний нарис діяльності Українського товариства охорони пам’яток історії та культури у Донбасі (друга половина 60–х – 80–ті роки ХХ ст.) - Принь, О.В. (Центр пам’яткознавства НАН України і Українського товариства охорони пам’яток історії та культури, 2009)
У статті висвітлено найбільш показові, важливі події, практичні заходи, які відображають історію діяльності обласних організацій Українського товариства охорони пам’яток історії та культури у Донбасі. В статье рассмотрены наиболее показательные, важные события, практические мероприятия, которые отображают историю деятельности областных организаций Украинского общества охраны памятников истории и культуры в Донбассе. The purpose of article is to cover the most typical occurrences, the practical actions reflecting history of the regional organizations of the Ukrainian Company of Protection of Monuments of History and Culture of Donbass, to discover forms and methods of work on the field of protection of monuments, to analyze experience of their work which will promote improvement of work of the state system of protection of monuments of a cultural heritage at the present stage.